Technical Note: Response time evolution of XR‐QA2 GafChromic™ film models. Issue 1 (12th December 2017) - Aldelaijan, Saad; Tomic, Nada; Papaconstadopoulos, Pavlos; Schneider, James; Seuntjens, Jan; Shih, Shelley; Lewis, David; Devic, Slobodan
Abstract : Purpose: To evaluate the response of the newest XR‐QA2 GafChromic™ film model in terms of postexposure signal growth and energy response in comparison with the older XR‐QA (Version 2) model. Methods: Pieces of film were irradiated to air kerma in air values up to 12 cGy with several beam qualities (5.3–8.25 mm Al) commonly used for CT scanning. Film response was scored in terms of net reflectance from scanned film images at various points in time postirradiation ranging from 1 to 7 days and 5 months postexposure. To reconstruct the measurement signal changes with postirradiation delay, we irradiated one film piece and then scanned it at different point times starting from 2" min and up to 3 days postexposure. Results: For all beam qualities and dose range investigated, it appears that the XR‐QA2 film signal completely saturated after 15 h. Compared to 15 h postirradiation scanning time, the observed variation in net reflectance were 3%, 2%, and 1% for film scanned 2" min, 20 min, and 3 h after exposure, respectively, which is well within the measurement uncertainty of the XR‐QA2 based reference radiochromic film dosimetry system. A comparison between the XR‐QA (Version 2) and the XR‐QA2 film response after several months (relative to their responses after 24 h) show differences in up to 8% and 1% for each film model respectively. Conclusions: The replacement of cesium bromide in the older XR‐QA (Version 2) film model with bismuth oxide in the newer XR‐QA2 film, while keeping the same single sensitive layer structure, lead to a significantly more stable postexposure response.